Encruzilhadas na trilogia Náusea: tessituras do silêncio na prosa ficcional de Edimilson de Almeida Pereira - Ferreirinha, Carlos Augusto dos Santos (2025)
This research aims to study the states of tension between poetic language and silence in the Nausea trilogy – composed of the works O Ausente, Um Corpo à Deriva, and Front – by Edimilson de Almeida Pereira, as an experimentation of forces and possibilities in transit. With this purpose, the study raises the following questions: To what extent do the textures of the works comprising the Nausea trilogy by Edimilson de Almeida Pereira push language to its limits, leading it to a state of “adrift language”? How does the process of language disarticulation, as a possibility of existence/resistance for the narrators of the Nausea trilogy, enable a crossing between the inside and outside of language, between word and silence? In what ways is the image of Exu – the Orisha of crossroads, the instaurator of another logic for organizing the world – articulated in the writing process of these novels? To test and answer these questions, the following hypotheses were formulated: the language woven in the works of the Nausea trilogy is strained to the point of being disarticulated as a symbolic-hermeneutic-rational understanding, leading it to a state of drift, of anti-language; the process of language disarticulation in these works, constructed in different ways, operates as the possibility of existence/resistance for the narrative voices, acting as a bridge that leads from the subject to the word and from the word to silence in a state of "hanging-word," enabling an experience of the word’s eroticism; the image of Exu is articulated, even when not explicitly presented, through the presence and discussion of Afro-diasporic cultures and the permeation of the sacred, as well as through the states of crossroads opened in the crossing of time, bodies, language, and silence in each of the novels. The study builds its theoretical-methodological foundation through a dialogical articulation between: the thoughts of Maurice Blanchot, Eni Orlandi, Annita Costa Malufe, and Charles Sanders Peirce regarding reflections on language and its crossings with silence; the theories of Antonin Artaud, Gilles Deleuze, and Félix Guattari to consider the processes of disarticulation of the body, time, and language; the literary experimentation proposals of Susan Sontag, Décio Pignatari, and Octavio Paz, as well as performance theories in Zumthor and Leda Maria Martins; and to address the issues and constructions of an Afro-diasporic-based literature in its relationship with the sacred, the study draws on the relational studies between ethnography and poetics by Edimilson de Almeida Pereira, Núbia Pereira Gomes, Prisca Agustoni, Édouard Glissant, and Dénètem Bona. This study is justified by its contribution to the critical reception of Pereira’s work, particularly his prose production, while also deepening relevant contemporary themes, such as the question of silence in literature and the development of an Afro-diasporic-based literature. By the end of this research, we observed the ways in which the weaving and refinement of silence operate as an anti-language, constantly moving between language and silence, making one the condition and the destiny of the other. Everything is organized through the perspective of the sacred, in which the figure of Exu, as the lord of paths and language, opens itself to a negative state of the word by becoming performance and communication of the ineffable